Fatores da satisfação e fidelidade de clientes na hotelaria: um estudo sobre a percepção dos gestores de hotéis - Farias, Adriana Cavalcante de (2010)
This Master of Science Thesis deals with the perception of hotels managers about the factors affecting the loyalty and satisfaction of its customers. It is surveyed a group of managers attending a hotel industry meeting and the results of their responses are compared with three surveys on tourist satisfaction and loyalty factors in Natal, Brazil, including international, national and regional tourist. The main findings suggest a divergence on the managers perception and the customer significant factors affecting satisfaction surveyed, but a certain convergence on the factors affecting loyalty. The research suggest a need for a customer satisfaction and loyalty measurement system in order to contribute for the alignment of managers perception and its customers evaluations